2011
DOI: 10.1007/s11434-011-4819-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide induced by nitric oxide mediates ethylene-induced stomatal closure of Arabidopsis thaliana

Abstract: Pharmacological, laser scanning confocal microscopic (LSCM), real-time PCR and spectrophotographic approaches are used to study the roles of hydrogen sulfide (H 2 S) and nitric oxide (NO) in signaling transduction of stomatal movement response to ethylene in Arabidopsis thaliana. In the present study, inhibitors of H 2 S synthesis were found to block ethylene-induced stomatal closure of Arabidopsis. Treatment with ethylene induced H 2 S generation and increased L-/D-cysteine desulfhydrase (pyridoxalphosphate-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 17 publications
3
71
0
Order By: Relevance
“…In plants, although originally associated with plant-pathogen interaction, it is now known to have an active role in diverse physiological processes such as oxidative stress, germination, and heat tolerance (Zhang et al, 2009a(Zhang et al, , 2009b(Zhang et al, , 2010a(Zhang et al, , 2010b(Zhang et al, , 2010dLi et al, 2013aLi et al, , 2013b. Recently, H 2 S has been proven to participate in ABA-or ethylene-induced stomatal closure in different plant species (García-Mata and Lamattina, 2010; Liu et al, 2011Liu et al, , 2012Jin et al, 2013). Moreover, it has been reported also that H 2 S induces stomatal opening (Lisjak et al, 2010(Lisjak et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In plants, although originally associated with plant-pathogen interaction, it is now known to have an active role in diverse physiological processes such as oxidative stress, germination, and heat tolerance (Zhang et al, 2009a(Zhang et al, , 2009b(Zhang et al, , 2010a(Zhang et al, , 2010b(Zhang et al, , 2010dLi et al, 2013aLi et al, , 2013b. Recently, H 2 S has been proven to participate in ABA-or ethylene-induced stomatal closure in different plant species (García-Mata and Lamattina, 2010; Liu et al, 2011Liu et al, , 2012Jin et al, 2013). Moreover, it has been reported also that H 2 S induces stomatal opening (Lisjak et al, 2010(Lisjak et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in methodological procedures concerning the isolation of epidermal strips and the timing of the treatments may result in the differential response of the guard cells to the H 2 S donors between Lisjak et al (2010) and this study. Liu et al (2011) showed that stomatal closure but not NO synthesis is impaired in an Arabidopsis mutant of the L-Cys desulfhydrase AtL-CDES gene. Therefore, they suggest that NO is acting upstream of H 2 S in ethyleneinduced stomatal closure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In plant systems, hydrogen sulfide has been found to play multiple physiological roles in plant growth, development and the acquisition of stress tolerance like heat tolerance (Lisjak et al 2010(Lisjak et al , 2013Li 2013). The novel functions of hydrogen sulfide have been uncovered in seed germination (Zhang et al 2010a;Li et al 2012a), root organogenesis (Zhang et al 2009a) and stomata movement (Lisjak et al 2010;Liu et al 2011;Jin et al 2013), as well as in alleviation in osmotic stress (Zhang et al 2009b), salt stress (Wang et al 2012), oxidative stress (Shan et al 2011, heavy metal stress (Zhang et al 2008(Zhang et al , 2010bChen et al 2013) and pathogen infection (Bloem et al 2011). Our previous results also showed that pretreatment with sodium hydrosulfide (NaHS), a hydrogen sulfide donor, could improve resistance of tobacco cells (Li et al 2012b) and maize seedlings (Li et al 2013a(Li et al ,b, 2014 to high temperature, but its mechanism is not fully clear.…”
Section: Introductionmentioning
confidence: 99%